Rapid Uplift, yet Slow Denudation of the Suckling‐Dayman Metamorphic Core Complex in Tropical Papua New Guinea - J. E. Österle; K. P. Norton; C. E. Lukens; T. A. Little; M. Mizera; S. M. Webber; K. Wilcken (Geophysical Research Letters)
Abstract A linear relationship between rates of physical erosion and chemical weathering is apparent in slowly eroding landscapes. Whether the relationship remains linear in rapidly eroding landscapes is less clear. Field‐based research into this relationship between erosion and weathering rates has largely been conducted in temperate climates with granitic bedrock. In tropical settings, the contribution of chemical mass loss to total denudation may approach, or even exceed, that of erosion. We report 10Be‐in‐quartz cosmogenic radionuclide and soil chemistry data from the Suckling‐Dayman Metamorphic Core Complex (SDMCC) in Papua New Guinea. Despite being exhumed at cm‐per‐year rates, its lower‐plate domed and striated morphology suggests minimal denudation, which is confirmed by our 10Be‐in‐quartz data (0.02–0.18 mm/yr). We suggest that rolling hinge‐style back‐rotation of the SDMCC's lower plate and the combination of a tropical climate and highly weatherable metabasalt bedrock have played a fundamental role in preserving the tectonic topography of this remarkable metamorphic core complex.